ESTIMASI KANDUNGAN KARBON (C) PADA SERASAH DAUN MANGROVE DI DESA LANSA, KECAMATAN WORI, KABUPATEN MINAHASA UTARA - Tidore, Fadli; Rumengan, Antonius; Sondak, Calvyn F.A.; Mangindaan, Remy E.P.; Runtuwene, Heard C.C.; Pratasik, Silvester B. (JURNAL PESISIR DAN LAUT TROPIS, 2018)
Global warming is one of the environmental issues related to climate change. Coastal blue carbon ecosystems such as mangrove and seagrass have ability to combat global warming. Mangrove ecosystem has an important ecological function in efforts to mitigate global warming, by carbon storage. This study was done in Lansa Village mangrove forest and focused on mangrove leaf litter. The purpose of this study was to estimate carbon content in mangrove leaf litter. Leaf litter samples were collected by using a 1x1 m2 litter trap, which was made of black nylon with a mesh size of about 0.2 cm, 8 traps were put under mangrove trees canopy, with a height of 1.5 m above sea level or at the highest tide. The samples were taken and observed every 7 days. The samples were analyzed by using Dry-Ash Method. The results showed that the average litter production of gram wet weight (Gbb) and gram dry weight obtained during the study were 122.97 gbb m2/28 days, 4.39 gbb m2/28 days, 47.69 gbk m2/28 days, 1.83 gb m2/day. The average of mangrove leaf litter biomass is 30.12 g m2. The highest amount of carbon storage in mangrove litter was 19.30 gram C. The average value of the percentage of carbon content of all plots was 31.38% per day. Based on these results the estimated amount of carbon removal in mangrove leaves was 2.16 t C ha-1 y-1 or 337.18 t C y-1.and 1,237.45 t CO2 y-1.Ekosistem mangrove memiliki fungsi ekologis yang sangat penting dalam upaya mitigasi pemanasan global, yakni sebagai penyerap dan penyimpan karbon Hutan mangrove juga memiliki peran sebagai penyerap karbon dioksida (CO2) dari udara sehingga sangat berguna untuk mitigasi perubahan iklim. Tujuan dari penelitian ini adalah untung mengestimasi kandungan karbon pada serasah daun mangrove di hutan mangrove Desa Lansa, Kecamatan Wori, Kabupaten Minahasa Utara. penelitian ini dilakukan menggunakan metode litter trap yang berukuran 1x1 m2, yang terbuat dari nylon berwarna hitam dengan ukuran mata jaring (mesh size) sekitar 0,2 cm, sebanyak 8 buah dipasang di bawah kanopi pohon mangrove, dengan ketinggian 1,5 m di atas permukaan air laut atau pada pasang tertinggi untuk menampung jatuhnya serasah dan diamati setiap 7 hari. Hasil penelitian diperoleh rata-rata produksi serasah gram berat basah (Gbb) dan gram berat kering yang didapat selama penelitian, sebesar 122,97 gbb/m2/28hr, 4,39 gbb/m2/hr, 47,69 gbk/m2/28hr, 1,83 gbk/m2/hr. rata-rata biomassa serasah daun mangrove sebesar 41,07. Jumlah simpanan karbon tertinggi pada serasah mangrove sebesar 19,30 gram C. Nilai rata-rata persentase kandungan karbon dari semua plot adalah sebesar 31,38% per hari, berdasarkan hasil penelitian jumlah estimasi kandungan karbon yang tersimpan pada serasah daun mangrove 2,16 ton/ha/tahun.